Comparative Analysis of Pepper Farming and Oil Palm Plantation Income in Wawobende Village, Sabulakoa District, South Konawe Regency - Puspitasari; Fausayana, Ine; Rosmawaty (International Journal of Technology and Education Research, 2026)
This study aims to determine: (1) the income generated from pepper farming compared to oil palm farming in Wawobende Village, Sabulakoa District, South Konawe Regency; and (2) whether there is a significant difference in income between pepper and oil palm farming in the same area. The sampling method employed in this research was a census approach. The total population consisted of 23 respondents, all of whom were included in the study, comprising pepper and oil palm farmers. Data were analyzed using farm income analysis and a Paired Sample t-test. The results indicate that: (1) the average income of respondents from pepper farming was Rp9,185,786.26 per season, while the average income from oil palm farming reached Rp46,500,845.61 per season; and (2) there is a statistically significant difference between income from pepper farming and oil palm farming. Based on the Paired Sample t-test, the significance value (2-tailed) was < 0.05 for both income variables, indicating that the difference is statistically significant. Therefore, oil palm farming is proven to generate significantly higher income compared to pepper farming in Wawobende Village